Effect of combining autoclave and ammoniation on nutritional value and in vitro digestibility of rice straw. Issue 1 (June 2021) - Muthia, D; Laconi, E B; Ridla, M; Jayanegara, A; Ridwan, R; Fidriyanto, R; Abdelbagi, M; Ramdani, H
Abstract: The use of rice straw for ruminant livestock has been restricted by the high fiber and low digestibility. This study aimed to evaluate the nutritional value and in vitro digestibility of rice straw processed by combining autoclave and ammoniation. The combination was performed to produce rice straw, which was able to digest by the rumen microorganism. The autoclave was conducted at 150°C, 1.2 atm, 60 minutes, whereas ammoniation used 3% urea. The study used a completely randomized design with four treatments i.e., untreated rice straw (A), rice straw + 3% urea (B), rice straw + autoclave (C), and rice straw + 3% urea + ensiling (D). Results revealed that urea addition increased (P<0.05) protein content of rice straw compared to the non-added urea. The pH of all sample treatments over 48 hours of in vitro analyses showed no significant difference, which means it with suit condition for the microorganism in the rumen (6.76– 6.82). The combination of rice straw + urea (B) showed higher (P<0.05) gas production in 24 and 48 hours in comparison to other treatments as well as increased (P<0.05). In conclusion, combining autoclave and ammoniation enhances the nutritional value and in vitro digestibility of rice straw.